Secondary components in Eugenia (Myrtaceae): Extraction and Efficiency as an antimicrobial in E. francavilleana and E. paracatuana (Research, Society and Development, 2022)
Organic extractives (OrgExt), also known as a secondary component of plants, have attracted interest of the scientific community in recent years due to their low toxicity and remarkable antimicrobial activity. This present work has aimed to increase knowledge about OrgExt of two Myrtaceae species of Brazilian flora: Eugenia francavilleana and E. paracatuana. OrgExtr of selected species were extracted by two different organic solvents to compare their efficiency and yieldness, namely: cylohexane/ethanol and hexane.  Paired T statistical method was used to evaluate yield of extraction process for both species. Quantitative determination of the main compounds presented in structures of plant tissues was performed (Klason lignin content, α-cellulose, holocellulose and polyoses). Inorganic components presented in ash of species were determined by EDS. Among organic solvents tested for extraction of essential substances, the most efficient was hexane, being Eugenia francavilleana the species that provided the highest yield of extracted oil. OrgExt demonstrated simultaneous efficiency in substitution of glycerol (plasticizer) in preparation of thermoplastic starch films and as antimicrobial agents, delaying and reducing appearance of microorganisms in these films. This study has increased knowledge of two species whose OrgExt had never been studied before and demonstrated a potential application.